Improving Human Learning and Performance at Indiana University. Issue 3 (March 2017) - Cho, Yonjoo; Boling, Elizabeth; Kwon, Kyungbin
Abstract : The Indiana University Instructional Systems Technology statement of purpose is, "We improve human learning and performance in diverse contexts." Our focus on learning and performance improvement includes K‐12 schools, higher education, business, industry, the government, military, and non‐profit organizations. This article gives an overview of the IST's background and history, key program elements (academic degree programs and leadership development programs), faculty's research and development activities, diverse students demographics and esteemed alumni (academics and practitioners), and future directions. We have led the instructional technology field through our commitment to remain a quality and forward‐thinking program.